Biomarkers for early diagnosis of pancreatic cancer. (March 2015) - Jenkinson, Claire; Earl, Julie; Ghaneh, Paula; Halloran, Christopher; Carrato, Alfredo; Greenhalf, William; Neoptolemos, John; Costello, Eithne
<x xml:space="preserve">Abstract</x> Pancreatic ductal adenocarcinoma is an aggressive malignancy with a 5-year survival rate of approximately 5%. The lack of established strategies for early detection contributes to this poor prognosis. Although several novel candidate biomarkers have been proposed for earlier diagnosis, none have been adopted into routine clinical use. In this review, the authors examine the challenges associated with finding new pancreatic cancer diagnostic biomarkers and explore why translation of biomarker research for patient benefit has thus far failed. The authors also review recent progress and highlight advances in the understanding of the biology of pancreatic cancer that may lead to improvements in biomarker detection and implementation.